THE EFFECT OF SPRAYING CHELATED CALCIUM AND CHELATED IRON ON THE VEGETATIVE AND FLOWERING GROWTH CHARACTERISTICS OF (GAZANIA SPLENDENS L.) - Sundus A. AL-Rahman,; Nawal M. Alwan, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
This study was aimed to investigate effect of spraying chelated Calcium and chelated Iron on the vegetative and floral growth characteristics of the Gazania plant , College of Agricultural Engineering Sciences, University of Baghdad in the  autumn season 2019-2020 and spring season 2020-2021 . The study was carried out as a factorial experiment in R.C.B.D. Design with three replications. Two factors were included in this study: foliar sprays of chelated Calcium at concentrations of 1, 2, 4 g L-1 (Ca1-Ca2-Ca3), respectively, in addition to control treatment, and chelated Iron in concentrations of 1and 2 g L-1 (Fe1-Fe2) respectively, in addition to control Fe0. The results showed a significant superiority in all vegetative and floral traits for both autumn and spring seasons. The treatment of spraying with chelated Calcium Ca4 was superior for most of vegetative and floral traits, as well as treatment of spraying with chelated Iron Fe2. The treatment combination Ca4Fe2 was also superior for plant height (cm), number of leaves (leaf.plant-1), chlorophyll content of leaves (mg.100 g-1 fresh weight), leaf area (cm2), fresh weight (g), dry weight (g), flowering period (days), flowering date (days), number of flowers (flower.plant-1), flower diameter (cm), (fresh weight of flowers, dry weight of flowers (g)).